PENGARUH CITRA MEREK DAN CELEBRITY ENDORSER TERHADAP KEPUTUSAN PEMBELIAN PRODUK WARDAH EXCLUSIVE MATTE LIPCREAM - De Ayuningrum Ratna Pertiwi, Luh (Jurnal Ilmu Manajemen (JIM), 2018)
This study is based on the phenomenon of the gap, the gap when Wardah issued Wardah Exclusive Matte Lip Cream which has a good brand image and are already using raline shah as endorsernya but sales experience fluctuations (increases when a new ad is shown, then the next month decline). The purpose of this study is to analyze and discuss the influence of brand image and celebrity endorser on purchasing decisions Wardah Exclusive Matte Lipcream. This study is a conclusive study. Using nonprobability sampling method. The sampling method used is judgmental sampling with the number of 110 respondents. Technique of collecting data using questionnaire with closed statement. This study uses the likert scale. The statistical analysis used is a multiple linear regression analysis with SPSS 18 for windows. The results showed that the variables of Brand Image are significant effect on the purchases decision with significant value of 0,008. Celebrity Endorser variables significantly influence the purchase decision with significant value of 0,002. Keywords: Brand Image; Celebrity Endorser; Purchase Decision